2015
DOI: 10.1016/j.enpol.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of residential solar power under uncertainty: Implications for renewable energy incentives

Abstract: We examine household adoption of solar PV using the option value framework. Uncertainty in benefits and costs leads to delay in investment timing. Discounted benefits from solar PV have to exceed investment cost by 60% to trigger investment. Policy incentives that reduce uncertainty in returns from solar PV are most effective. a b s t r a c tMany incentives at the state and federal level exist for household adoption of renewable energy like solar photovoltaic (PV) panels. Despite generous financial incentives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(32 citation statements)
references
References 14 publications
(18 reference statements)
1
28
0
Order By: Relevance
“…However, stability in energy costs via solar installation is also an important benefit to adopters. Other work has found that reducing long term economic uncertainty is an important factor in solar adoption [14], and retail electric rates in an area can drive solar technology adoption [15]. Other research suggests the importance of non-economic factors that influence a prospective customer's decision to adopt solar technology.…”
Section: Household Solar Technology Adoption Researchmentioning
confidence: 99%
“…However, stability in energy costs via solar installation is also an important benefit to adopters. Other work has found that reducing long term economic uncertainty is an important factor in solar adoption [14], and retail electric rates in an area can drive solar technology adoption [15]. Other research suggests the importance of non-economic factors that influence a prospective customer's decision to adopt solar technology.…”
Section: Household Solar Technology Adoption Researchmentioning
confidence: 99%
“…Depreciation benefits are calculated for each year by figuring the allowable depreciation number, multiplying by the marginal tax rate, and discounting the benefit back into present value terms. The allowable depreciation benefit in a given year 1 A more recent and very interesting development in the field is the application of real options analysis to the optimal timing of PV investments (Bauner and Crago, 2013;Ansar and Sparks, 2009). This approach has not yet incorporated the complexities of tariff schedules, taxes, time-of-use, etc.…”
Section: Model Specificationmentioning
confidence: 99%
“…Solar energy use and time-of-use tariffs applied and available for low voltage consumers is already a reality in most European Countries [1][2][3][4][5][6]. In Brazil, despite of having one of the highest solar energy potential in the world, its use of solar energy is still incipient .…”
Section: Introductionmentioning
confidence: 99%